Is Disturbed Transfer of Learning in Callosal Agenesis due to a Disconnection Syndrome? - T. Imamura; A. Yamadori; Y. Shiga; M. Sahara; H. Abiko (Behavioural Neurology)
Disturbed intermanual transfer of tactile learning in callosal agenesis has been interpreted as a sign of disconnection syndrome. We observed this sign in one of four acallosal patients with a conventional form-board task, and tried to elucidate the nature of the deficit. The form-board performance of the patient with disturbed transfer of learning totally depended on motor skill, while the other acallosals and normal controls executed the task based on spatial and somesthetic information. All acallosals and normals, however, failed to show transfer of learning with another tactile task which needed motor skill but not spatial-somesthetic information. These findings suggest that the task-performing strategies in form-board learning change the state of interhemispheric transfer. Unimanual learning effect is transferred if spatial-somesthetic information is acquired in the process of learning, but is not transferred if motor skill is the exclusive content of learning. We conclude that disturbed “transfer” of learning in some acallosals is not a true disconnection sign. It should be attributed to a lack of appropriate strategy, as a result of ineffective problem solving in tactile tasks.